Bank regulation, risk and return: Evidence from the credit and sovereign debt crises - Hoque, Hafiz; Andriosopoulos, Dimitris; Andriosopoulos, Kostas; Douady, Raphael (Journal of Banking & Finance, 2015)
In this paper, we analyze whether regulation reduced risk during the credit crisis and the sovereign debt crisis for a cross section of global banks. In this regard, we examine distance to default (Laeven and Levine, 2008), systemic risk (Acharya et al., 2010), idiosyncratic risk, and systematic risk. We employ World Bank survey data on regulations to test our conjectures. We find that regulatory restrictions, official supervisory power, capital stringency, along with private monitoring can explain bank risk in both crises. Additionally, we find that deposit insurance schemes enhance moral hazard, as this encouraged banks to take on more risk and perform poorly during the sovereign debt crisis. Finally, official supervision and private monitoring explains the returns during both crisis periods.